2012
DOI: 10.1002/ana.23733
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in lacunar strokes: The SPS3 trial

Abstract: Objective Lacunar strokes are a leading cause of cognitive impairment and vascular dementia. However, adequate characterization of cognitive impairment is lacking. The aim of this study was to estimate the prevalence and characterize the neuropsychological impairment in lacunar stroke patients. Methods All English-speaking participants in the SPS3 trial (NCT: 00059306) underwent neuropsychological testing at baseline. Raw scores were converted to z-scores using published norms. Those with impairment (z≤-1.5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 37 publications
3
88
2
6
Order By: Relevance
“…With an aging population and a decline in mortality after stroke,4 the rates of poststroke cognitive impairment will increase. Despite being as common as other neurological deficits, such as motor and sensory, cognitive impairment is often overlooked in the follow‐up of stroke survivors unless they have progressed to dementia 5. This may well be because these patients are able to maintain some level of personal independence despite poor cognitive recovery 6…”
Section: Introductionmentioning
confidence: 99%
“…With an aging population and a decline in mortality after stroke,4 the rates of poststroke cognitive impairment will increase. Despite being as common as other neurological deficits, such as motor and sensory, cognitive impairment is often overlooked in the follow‐up of stroke survivors unless they have progressed to dementia 5. This may well be because these patients are able to maintain some level of personal independence despite poor cognitive recovery 6…”
Section: Introductionmentioning
confidence: 99%
“…The observation of impaired processing speed, motor dexterity and executive function was consistent with the impairment pattern hypothesised for subcortical ischaemic disease. 46 On the other hand, the observation of episodic memory deficits was a novel aspect of the study given that incident lacunes have been reported to impact processing speed and motor control but not memory. 46 The authors emphasised that mild cognitive impairment found in half of the participants is an important clinical sequela of lacunar stroke, which in turn is more prevalent than physical disability defined by m-Rankin score ≥2 (33 %) and present in 41 % of patients with no significant disability (m-Rankin score 0-1' Barthel index score 100).…”
Section: Recent Advances and Therapeutic Strategiesmentioning
confidence: 99%
“…46 On the other hand, the observation of episodic memory deficits was a novel aspect of the study given that incident lacunes have been reported to impact processing speed and motor control but not memory. 46 The authors emphasised that mild cognitive impairment found in half of the participants is an important clinical sequela of lacunar stroke, which in turn is more prevalent than physical disability defined by m-Rankin score ≥2 (33 %) and present in 41 % of patients with no significant disability (m-Rankin score 0-1' Barthel index score 100). It is speculated that the cognitive effects of lacunar stroke are at least as important as disability related to motor or sensory deficits, and can occur in their absence.…”
Section: Recent Advances and Therapeutic Strategiesmentioning
confidence: 99%
See 2 more Smart Citations